Efektivitas Pelatihan Pengolahan Kunyit terhadap Pembentukan Karakter Tanggung Jawab Santriwati di IMBS Miftahul Ulum Pekajangan - Fuad, Asfal; Wirotomo, Tri Sakti (Jurnal Alwatzikhoebillah : Kajian Islam, Pendidikan, Ekonomi, Humaniora, 2026)
Character education is a central objective of Islamic education, particularly in pesantren, which emphasize moral development, independence, and responsibility among students. However, character education practices remain predominantly normative and provide limited measurable experiential learning. This study aims to examine the effectiveness of turmeric (Curcuma longa) processing training in fostering responsibility character among female students (santriwati) at IMBS Miftahul Ulum Pekajangan. A quantitative approach was employed using a one-group pretest–posttest design. Data were collected through a responsibility character questionnaire that demonstrated acceptable validity and high reliability (Cronbach’s Alpha = 0.87). Data analysis involved descriptive statistics and a paired sample t-test. The results revealed a significant improvement in responsibility character scores after the training, with a mean difference of 13.95 points and a significance value of p < 0.05. These findings indicate that simple, context-based turmeric processing training effectively enhances santriwati’s responsibility toward personal health management, task performance, and social care within the pesantren environment. This study contributes an integrative character education model that combines Islamic values, reproductive health awareness, and life skills through the utilization of local natural resources.